Determinants of sovereign debt ratings in clusters of European countries - effects of the crisis - Proença, Catarina (2022)
Purpose: This paper studies the determinants of the sovereign debt ratings provided by the three main rating agencies for 32 European countries. It verifies the clusters of countries existing for each of the agencies, considering regional bias, and then analyzes whether the determinants were different before and after the global financial crisis. It also aims to explain how the determinants are taken into account for rich and developing countries, using a sample for the period between 2001 and 2008 and the period between 2009 and 2016. Design/methodology/approach: To this purpose, we perform panel data estimation using an Ordered Probit approach. Findings: This method shows that for developing countries after the crisis, the relevant explanatory variables are the unemployment rate and the presence in the Eurozone. For rich countries, the inflation rate is pivotal after the crisis period. Originality/value: This paper is the first to use a clustering methodology within sovereign debt rating literature, grouping the countries into cohesive clusters according to their sovereign debt ratings along the proposed time frame. Moreover, it explains which countries belong to strong or weak groups, according to the rating agencies under discussion; and, in these groups, it identifies the sovereign rating determinants.